2017
DOI: 10.1007/s00122-017-2922-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of multi-environment trials for genomic selection based on crop models

Abstract: Key message We propose a statistical criterion to optimize multi-environment trials to predict genotype × environment interactions more efficiently, by combining crop growth models and genomic selection models.AbstractGenotype × environment interactions (GEI) are common in plant multi-environment trials (METs). In this context, models developed for genomic selection (GS) that refers to the use of genome-wide information for predicting breeding values of selection candidates need to be adapted. One promising wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 70 publications
0
55
0
Order By: Relevance
“…Our results were obtained with individuals from the training population chosen at random. Other studies (Akdemir et al 2015; Isidro et al 2015; Rincent et al 2017) found that optimizing the training population to select the most predictive individuals instead of using a random sample increases the predictive ability. We would therefore expect that our results are the baseline for the gain that could be achieved by using replaced phenotyping when the training population is optimized.…”
Section: Discussionmentioning
confidence: 98%
“…Our results were obtained with individuals from the training population chosen at random. Other studies (Akdemir et al 2015; Isidro et al 2015; Rincent et al 2017) found that optimizing the training population to select the most predictive individuals instead of using a random sample increases the predictive ability. We would therefore expect that our results are the baseline for the gain that could be achieved by using replaced phenotyping when the training population is optimized.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the complexity of plant responses to stressed conditions resulting from G  ×  E interactions, the difficulties in determining all possible genetic responses to all possible combinations of environments and the inability to phenotype large breeding populations avoiding confounding weather effects (Reynolds and Tuberosa 2008) hamper accurate predictions of GY. One potential approach to address this challenge would be to integrate crop growth models with genomic selection models (Rincent et al 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Crop growth models allow for a more explicit understanding of the underlying causes of the GxE patterns, under the assumption that the crop growth model is sensitive enough to all the meteorological information that is relevant for GxE. For example, Rincent et al (2017) proposed an optimization criterion to identify those locations that allow for a better prediction of wheat flowering time in other locations. This optimization criterion was applied to wheat flowering time data simulated with the Sirius model (Jamieson et al 1998) and validated on real data in field trials across France.…”
Section: Structure Of the Tpementioning
confidence: 99%